Temporal aspects of copper homeostasis and its crosstalk with hormones - Peñarrubia, Lola; Romero, Paco; Carrió-Seguí, Angela; Andrés-Bordería, Amparo; Moreno, Joaquín; Sanz, Amparo (Frontiers in Plant Science, 2015)
To cope with the dual nature of copper as being essential and toxic for cells, plants temporarily adapt the expression of copper homeostasis components to assure its delivery to cuproproteins while avoiding the interference of potential oxidative damage derived from both copper uptake and photosynthetic reactions during light hours. The circadian clock participates in the temporal organization of coordination of plant nutrition adapting metabolic responses to the daily oscillations. This timely control improves plant fitness and reproduction and holds biotechnological potential to drive increased crop yields. Hormonal pathways, including those of abscisic acid, gibberellins, ethylene, auxins, and jasmonates are also under direct clock and light control, both in mono and dicotyledons. In this review, we focus on copper transport in Arabidopsis thaliana and Oryza sativa and the presumable role of hormones in metal homeostasis matching nutrient availability to growth requirements and preventing metal toxicity. The presence of putative hormone-dependent regulatory elements in the promoters of copper transporters genes suggests hormonal regulation to match special copper requirements during plant development. Spatial and temporal processes that can be affected by hormones include the regulation of copper uptake into roots, intracellular trafficking and compartmentalisation, and long-distance transport to developing vegetative and reproductive tissues. In turn, hormone biosynthesis and signalling are also influenced by copper availability, which suggests reciprocal regulation subjected to temporal control by the central oscillator of the circadian clock. This transcriptional regulatory network, coordinates environmental and hormonal signalling with developmental pathways to allow enhanced micronutrient acquisition efficiency.